Effect of Visible Light on Catalytic Hydrolysis of P-nitrophenyl Palmitate by the Pseudomonas Cepacia Lipase Immobilized on Sol–Gel Support - Ponnarasy, Ganasen; Khan, Maksudur R.; M., Abul Kalam; Mohd Sabri, Mahmud (Springer Berlin Heidelberg, 2014)
This paper demonstrates Pseudomonas cepacia lipase catalyzed hydrolysis of p-nitrophenyl palmitate under irradiation of light with wavelengths of 250–750 nm. The reaction follows Michaelis–Menten Kinetics and the light irradiation increases the overall rate of hydrolysis. Using Lineweaver–Burk plot K M and V max values for the reaction in presence of light are found to be 39.07 and 66.67 mM/min/g, respectively; while for the same reaction under dark condition, the values are 7.08 and 10.21 mM/min/g. The linear form of enzyme dependent rate of reaction confirms that no mass-transfer limitations are present and the reaction is a kinetically controlled enzymatic reaction.